2017
DOI: 10.1101/160036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced proofreading governs CRISPR-Cas9 targeting accuracy

Abstract: 22alanine weakens target binding 11 , the affinities of these variants for on-target and PAM-distal 46 mismatched substrates were similar to WT SpCas9 (Figure 1b, Extended Data Figure 1a, 2b), 47

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
279
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(294 citation statements)
references
References 26 publications
15
279
0
Order By: Relevance
“…We hypothesized that the position of the mobile HNH nuclease domain directly couples to R-loop progression, allowing it to influence its free-energy landscape. This hypothesis is based on the following key observations: First, ensemble FRET experiments 49 detected two dominant Cas9 conformers with distinct HNH states, and single-molecule FRET studies have identified a third intermediate conformer 40,41,51 -matching the number of R-loop states we find; Second, the relative position and occupancy of the HNH states is affected by R-loop mismatches 40,41,51 , while the Cas9 can only sense mismatches by hybridizing the sgRNA with the target DNA. To test this hypothesis, we mimicked the experiments of Dagdas et al 40 by calculating the time evolution of the occupancy for each of the microscopic states in the DNA-bound Cas9 landscape for three target sequences (Fig.…”
Section: R-loop Propagation Drives Cas9 Conformation Dynamicsmentioning
confidence: 83%
See 2 more Smart Citations
“…We hypothesized that the position of the mobile HNH nuclease domain directly couples to R-loop progression, allowing it to influence its free-energy landscape. This hypothesis is based on the following key observations: First, ensemble FRET experiments 49 detected two dominant Cas9 conformers with distinct HNH states, and single-molecule FRET studies have identified a third intermediate conformer 40,41,51 -matching the number of R-loop states we find; Second, the relative position and occupancy of the HNH states is affected by R-loop mismatches 40,41,51 , while the Cas9 can only sense mismatches by hybridizing the sgRNA with the target DNA. To test this hypothesis, we mimicked the experiments of Dagdas et al 40 by calculating the time evolution of the occupancy for each of the microscopic states in the DNA-bound Cas9 landscape for three target sequences (Fig.…”
Section: R-loop Propagation Drives Cas9 Conformation Dynamicsmentioning
confidence: 83%
“…The physical insights generated by the free-energy landscapes we extract could also help rational proteinreengineering efforts aimed at producing high-fidelity Cas9 variants that maintain high on-target efficiency 39,51,56 . For SpCas9, we find that the barrier between the intermediate and closed states is tuned to extend the cleavage specificity beyond the seed, without affecting on-target efficiency (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55,66 Numerous in vitro and in vivo experiments have revealed that DNA binding is significantly more promiscuous than cleavage, and recent biophysical studies have highlighted the conformational rearrangements that are required for driving DNA-bound SpyCas9 into a catalytically active state. [67][68][69][70] Target-strand cleavage by the HNH domain precedes nontarget-strand cleavage by the RuvC domain, 71,72 and mutations that modulate either DNA interactions or Cas9 conformational dynamics can significantly enhance the fidelity of RNA-guided DNA cleavage. 69,[73][74][75][76] Two other observations regarding DNA cleavage deserve emphasis.…”
Section: Crispr-cas Diversity and Classificationmentioning
confidence: 99%
“…[67][68][69][70] Target-strand cleavage by the HNH domain precedes nontarget-strand cleavage by the RuvC domain, 71,72 and mutations that modulate either DNA interactions or Cas9 conformational dynamics can significantly enhance the fidelity of RNA-guided DNA cleavage. 69,[73][74][75][76] Two other observations regarding DNA cleavage deserve emphasis. First, although Cas9 is often described as an enzyme that generates blunt DSBs, biochemical experiments with SpyCas9 clearly demonstrate that the RuvC nuclease domain catalyzes additional ''trimming'' of the nontarget strand in the 3¢/5¢ direction, upstream of the cleavage site.…”
Section: Crispr-cas Diversity and Classificationmentioning
confidence: 99%